Gender relations, urban flooding, and the lived experiences of women in informal urban spaces. Issue 3 (2nd July 2020) - Singh, Deepshikha
ABSTRACT: This study draws on qualitative data about gendered vulnerabilities and resilience in situations of urban flooding in the Mumbai Metropolitan Region, India. Women in informal urban spaces comprise marginalized groups who face greater risks in times of disaster owing to their inferior socioeconomic status and the hazardous geographical space they occupy. This study provides insights into the lived experiences of women in such spaces that are shaped by unequal gender relations and flooding. Women's narratives are analyzed and presented as part of my research findings. Unequal gender relations, combined with socioeconomic disadvantage, are important factors for their vulnerability and limited resilience. The perspectives of urban disadvantaged women, which have been long ignored, need to be actively integrated into disaster risk reduction planning. The implications of a gendered approach to disaster risk reduction by prioritizing the empowerment of urban disadvantaged women is discussed and suggested.